FAKTOR-FAKTOR YANG MEMENGARUHI KEPEMIMPINAN PENDIDIKAN - Marta Lia Ningtyas; Mutia Aisha Wibowo; Tsasya Ridha Sholekhah; Farah Putri Ramadhani (STKIP Subang, 2026)
Educational leadership is the ability of a leader to influence, guide, direct, and mobilize all school residents to achieve educational goals effectively and efficiently. The success of the implementation of education is not only determined by the availability of facilities and infrastructure, but also influenced by the quality of leadership in managing existing resources. This study aims to analyse the factors that affect educational leadership and explain the importance of leadership in improving the quality of education. The research uses a qualitative method with a literature study approach (library research). Data is obtained through the collection and analysis of various written sources, such as books, scientific articles, journals, and previous research results that are relevant to the research topic. Data analysis is carried out descriptively through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that educational leadership is influenced by internal factors which include the ability and expertise, personality, and morality of the leader, and external factors which include organizational culture, rewards, and education policies. The interaction between internal and external factors determines the effectiveness of leadership in creating a conducive learning environment, increasing teacher motivation and professionalism, strengthening cooperation between school residents, and encouraging improvement of the quality of education. Thus, the development of educational leadership needs to be carried out comprehensively through improving the competence of leaders and creating a supportive organizational environment so that educational goals can be achieved optimally.